UNDERSTANDING HADITH CONTRADICTIONS IN THE USE OF PROHIBITED SUBSTANCES FOR THE TREATMENT OF DIABETES MELLITUS - Fauziyyah, Wafa; Nurhayati, Via (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
This article reveals the crucial problem of treatment using pork-based insulin. It has been widely discussed by the public and reaped controversy pros and cons in the realm of religion. Meanwhile, treatment is one of the creature's efforts to the Creator, which is one of the protections in maintaining adh dharuriyat al khams on the preservation of the soul. The controversy arises because of the insulin containing forbidden substances consumed in diabetes treatment. There are contradictory hadiths that allude to treatment using the haram. So this paper aims to find out the correct and correct understanding of the compromise between the two contradictory traditions by using the science of Mukhtalaf al-Hadiṡ and what are the implications of the hadith of treatment using something forbidden on the use of insulin in people with diabetes. The analysis used in resolving the two contradictory traditions is the al-jam'u wa al-taufiq method. The proof that the use of forbidden substances is prohibited is known by the rapid advancement of technology and knowledge, of course, many new products have emerged to be able to replace the use of forbidden substances, except in emergencies.